TANTANGAN PEMBELAJARAN IPS TERHADAP ISU GLOBAL TEKNOLOGI - Febriyanti, Intan; Raya, Mutiara; Septa Wijaya, Radit (Prodi Pendidikan IPS, Universitas Tanjungpura, 2025)
This study aims to address global issues in technology that are challenges in social studies learning in order to improve students' understanding or appeal and skills in social studies learning. The method used is a literature study by reviewing relevant literature on inquiry-based learning models, problem-based learning, expository, and contextual. The results of the study indicate that the application of active learning strategies, such as inquiry and problem-based learning, can encourage students to think critically, creatively, and improve data analysis and communication skills. In addition, social studies learning that is integrated with real experiences is considered effective in shaping students' social attitudes and empathy. This study recommends that teachers optimize variations in learning strategies according to student characteristics and materials, in order to achieve social studies education goals holistically.